The Effectiveness of 80% Kefir Gel Against The Overview The Number of Fibroblasts in Healing Cuts Mice (Mus Musculus) - Dessy Abdullah; Budi Yulhasfi Febrianto; Nadia Purnama Dewi; Ade Teti Vani; Fitria Chairal Ulfah (poltekkes kemenkes mataram, 2022)
Several sources cause skin tissue damage. Kefir probiotics, made from fermented cow's milk, are believed to remove scars during use. Kefir involves a series of immune processes, acute and chronic inflammatory processes, cell division cell migration, chemotaxis, and various differentiations. This research determines the histopathological fibroblast cells in the wound healings in mice (Mus musculus) given 80% kefir probiotic. The method of research was the posttest-only control group experimental design. Mus musculus aged eight weeks with a bodyweight of 18-40 grams were taken in two groups randomly with 32 Mice. The result is that fibroblasts in the negative control group had a smaller mean of 10,25 compared to the mean number of fibroblast cells in the 80% Kefir group, which was 25,18. Thus, it was proven that the effectiveness of Kefir probiotics of wound healing in mice (Mus musculus) was given 80% kefir probiotic (p=0,000 <0.05). There is an effect of kefir probiotic on the healing of cuts in mice based on the calculation of the number of fibroblast cells.